2020
DOI: 10.3390/nano10030485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Level and Mechanisms of Toxicity of Carbon Nanotubes, Carbon Nanofibers, and Silicon Nanotubes in Bioassay with Four Marine Microalgae

Abstract: Nanoparticles (NPs) have various applications in medicine, cosmetics, optics, catalysis, environmental purification, and other areas nowadays. With an increasing annual production of NPs, the risks of their harmful influence to the environment and human health is rising. Currently, our knowledge about the mechanisms of interaction between NPs and living organisms is limited. Additionally, poor understanding of how physical and chemical characteristic and different conditions influence the toxicity of NPs restr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 86 publications
3
35
0
Order By: Relevance
“…Carbon nanofibers also demonstrated relatively high embryotoxicity (48 h LC 50 about 25 mg/L), and carbon nanotubes were the least toxic (48 h LC 50 , 65–75 mg/L). These results are consistent with our previous research with the same NPs tested in microalgae [ 43 , 44 ] and bivalves [ 45 ], where the highest toxicity was observed for the samples of metal and metal sulfide NPs, followed by silicon nanotubes, carbon nanofibers, and carbon nanotubes.…”
Section: Discussionsupporting
confidence: 93%
“…Carbon nanofibers also demonstrated relatively high embryotoxicity (48 h LC 50 about 25 mg/L), and carbon nanotubes were the least toxic (48 h LC 50 , 65–75 mg/L). These results are consistent with our previous research with the same NPs tested in microalgae [ 43 , 44 ] and bivalves [ 45 ], where the highest toxicity was observed for the samples of metal and metal sulfide NPs, followed by silicon nanotubes, carbon nanofibers, and carbon nanotubes.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, a significant number of studies have been devoted to the effect of micro and nanosized particles of various origins on marine organisms [ [22] , [23] , [24] , [25] , [26] , [27] ]. Amongst them, some are devoted to the effects of coal particles and are presented in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of C nanomaterials in algae can also be due to the presence of heavy metal impurities due to low-efficiency manufacturing process (which, for the lowest manufacturing processes, can constitute up to 99.9% of the total production output 68 ). A recent study has shown that metal impurities in C nanotubes affect the esterase activity of the algae Attheya ussuriensis , Chaetoceros muelleri , Heterosigma akashiwo and Porphyridium purpureum (with the latter showing the lowest changes) 69 . It should however be noted that, in the present study, no metal impurities were detected (Figs.…”
Section: Resultsmentioning
confidence: 99%